Performance Evaluation of Electronic Control System in Series-Parallel Hybrid Vehicle: A Simulation Study - Permatasari, Jelita; Santoso, Dian Budhi; Sunardi, Egi; Laili, Maria Bestarina (International Journal of Electronics and Communications Systems, 2025)
The increasing contribution of the transportation sector to global emissions has driven the development of hybrid electric vehicles (HEVs) as a practical solution to reduce environmental impact. The effectiveness of HEVs is highly dependent on electronic control systems that regulate power distribution between the internal combustion engine (ICE), electric motor, generator, and battery in real time under various operating conditions. This study aims to evaluate the performance of the electronic control system implemented using Stateflow in a simulated series-parallel hybrid electric vehicle. The research methodology involves simulating the vehicle model in MATLAB/Simulink, which integrates Stateflow to design and manage the logic and operational mode transitions. A continuous closed-loop feedback structure is used to facilitate real-time control decisions, guided by input variables such as throttle position, vehicle speed, and battery State of Charge (SoC). Various driving scenarios are simulated, including acceleration, steady cruising, deceleration, and energy recovery during braking. Simulation results show that the designed electronic control system can maintain operational stability with engine efficiency reaching 92%, battery power utilization up to 65%, and electronic transitions between modes (EV, HEV, regenerative) in less than 0.2 seconds, demonstrating a 40% improvement in response compared to conventional electronic control models. These findings confirm the potential of Stateflow-based electronic control approaches in creating more responsive and efficient hybrid vehicle propulsion systems, while supporting the development of low-emission transportation technology